Emotional competence and problem behavior of left-behind preschool children—the roles of self-regulation and authoritative grandparenting styles - Luo, Lanlan; Jin, Shan; Huang, Qi (Frontiers in Education, 2025)
IntroductionWhen parents migrate to other cities for work, their children who are left behind show a high prevalence of behavioral problems, which affect social function. Although previous studies have found that emotional competence significantly predicts problem behavior, little is known about the mechanism(s) through which self-regulation and authoritative grandparenting styles affect emotional competence and problem behavior. This study examined the associations between emotional competence and problem behavior of preschoolers and the mediating role of self-regulation and the moderating role of authoritative grandparenting styles.MethodsParticipants included 449 left-behind preschool children (46.3% girls, mean age = 53.65 months). Grandparents reported their parenting styles with children and teachers reported children’s problem behavior. Children’s emotional competence and self-regulation were completed one-on-one by trained research assistants, following a standard protocol.ResultsThe results revealed that children’s emotional competence is negatively related to problem behavior. Self-regulation partially mediates the effects of emotional competence on problem behavior. Authoritative grandparenting styles moderated the relationship between emotional competence and problem behavior in children, but not the relationship between self-regulation and problem behavior. Significantly, authoritative grandparenting styles enhanced the promoting effect of emotional competence and reduced children’s problem behavior.DiscussionOur findings underscore the importance of intrinsic elements of child self-regulation, as well as adopting more authoritative parenting behaviors in their daily interaction with children, on developing stronger emotional competence and reducing problem behavior in preschoolers.